Analisis Tiga Metode Evaluasi Usability Untuk Menemukan Permasalahan Usability Pada Situs Kecamatan Lowokwaru - Ishak Robin Simorangkir; Fatwa Ramdani; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
This study aims to compare the effectiveness of three usability evaluation methods in usability problems on the Lowokwaru District website and to identify and classify the types of problems found. The method used is the usability evaluation method which involves users in it, namely: usability testing (N = 10), interviews (N = 10), and surveys (N = 30). The data collected by each method comes from site users who live in Lowokwaru District. The three methods identified a total of 35 usability problems: 46% via usability testing, 34% via survey, and 20% via interview method. These usability problems were classified into 5 categories and 21 problem topics. Usability testing was successful in identifying most of the problem categories (80%) followed by the survey (60%) and the interviews were successful in identifying the number of problem categories (40%). Usability testing is the most effective method to identify usability problems followed by survey and interview methods. Although usability testing identifies more usable problems than the survey and interview methods, no single method can identify all the problems that are visible to users. Therefore, a combination of these three methods is needed, because they complement each other in finding problems on a website.